Two Birds with One Phone: The Role of Mobile Use in the Daily Practices of Remote Information Work - Swain, Vedant Das; Williams, Shane; Fourney, Adam; Iqbal, Shamsi (CHIWORK 2022, 2022)
Without the constraints of traditional work environments, information workers can work anywhere, but also any way — interleaving nonwork activities into work hours and vice versa. The mobile provides affordances that support work–nonwork transitions in a way that was not possible from the office. However, it is unclear if and how information workers leverage their mobiles to achieve flexible work practices at home. While uncontrolled flexibility can conflict with productivity, the remote setting suppresses certain explicit opportunities to use a mobile device, e.g. during a commute, due to which people may not be engaging in mobile based flexible work. We aim to describe these mobile use patterns for remote information work to inform better ways to balance work and nonwork needs. We present early evidence from a survey of 118 information workers, a data logging field study of 23 information workers, and follow up data-walkthrough interviews. We found that even though mobiles were used for meetings at home, majority of mobile use was for short nonwork activities. We also found that the mobile can help multitask between work and nonwork roles when remote. At the same time, the mobile supports sedentary digital breaks, despite the flexible nature of information work. These results highlight the role of the mobile device in facilitating a future with flexible work practices to rethink traditional “desk jobs”.